Penegakan Hukum Terhadap Pemilik Bangunan di Kawasan Konservasi Mangrove Gunung Anyar Tambak Surabaya - Pramesti, Savira Rizka (Universitas Negeri Surabaya, 2021)
Surabaya East Coast (Pamurbaya) protected area is a region of many changes due to the city of Surabaya with the characteristics of rapid development, high population growth and increasing housing needs has forced the city of Surabaya to expand uncontrollably, causing many buildings to stand out according to the system Surabaya City space, so building permits cannot be issued because they do not go through the spatial use permit procedure. It has been regulated in Article 139 of Law Number 1 of 2011 concerning Housing and Settlement Areas that stipulates a prohibition on building housing and / or settlements outside areas specifically designated for residential housing. But the fact is there is still a residential area in the mangrove conservation area of ​​Mount Anyar, Surabaya. This study aims to reveal how law enforcement and the constraints of law enforcement on buildings in the mangrove conservation area of ​​Gunung Anyar, Surabaya. The research method used is empirical juridical. Data sources were obtained from primary and secondary data which were then analyzed descriptively qualitatively. The results of the study show that up to now the law enforcement is still up to written warnings, namely sending summons and warning letters to housing developers and sticking IMB violation stickers on the building that is in violation. Until now, no strict sanctions have yet been carried out. Law enforcement has not been carried out because there are elements in law enforcement that have not been fulfilled. The elements that have not been fulfilled include the elements of making laws, elements of law enforcement, and environmental elements. Constraints faced in law enforcement include the absence of local regulations on the strategic plan of the Pamurbaya protected area, the limitations of law enforcement personnel to carry out surveillance and law enforcement, supervision and passive control, the level of awareness of developers and communities residing in the conservation area with feel the building is legal because it has a letter from the village in the form of sporadic. From this the authors gave suggestions, among others, first, the Head of the Cipta Karya and Spatial Planning Office immediately gave a warrant to the Satpol PP to immediately conduct control at the next stage so that there were no more buildings located in the conservation area of ​​the Anyar Tambak mountain in Surabaya, the government in the fiscal year 2021 can add to the needs of Satpol PP members so that control activities in the Pamurbaya area can be realized immediately, the boundaries of the conservation area are not only concrete pillars but are accompanied by clearly visible information boards, conduct routine supervision and coordinate with officers both at relevant agencies, sub-districts and kelurahan, local RT / RW through applications on smartphones in the form of group chat and the like to facilitate coordination and accelerate complaints if there are building violations, disclosure of information on spatial planning by providing internet facilities in the village and sub-district to always be u update information about the Surabaya city spatial plan and make it easy to provide socialization to the local community. Keywords: Pamurbaya, Conservation Area, Law Enforcement